2021
DOI: 10.1021/acsami.1c10021
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Interfacial and Structural Heterogeneity of Ti3C2Tx MXene Etched with CoF2/HCl by Integrated in Situ Thermal Analysis

Abstract: Ti 3 C 2 T x MXene is a member of the recently discovered two-dimensional early transition metal carbide and nitride family of MXenes with potential applications in energy storage and heterogeneous catalysis at elevated temperatures. Here, we apply a suite of in situ techniques to probe Ti 3 C 2 T x MXene's thermal evolutions, including in situ X-ray diffraction (XRD), in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), and integrated thermogravimetry−differential scanning calorimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…CoF2-MXene has a distinct shoulder to the (002) peak between 2θ = 0.5 -1.0°, reflecting the presence of a pillared structure. 27 Using this shoulder at 0.77° to calculate a c lattice parameter of 36 Å reveals layering with ultra-large interlayer spacing for CoF2-MXene. Smaller cations with lower charges, such as Na + or K + , lead to larger interlayer spaces than multivalent cations like Al 3+ due to their smaller hydration shell, allowing two layers of cations and associated water within an interlayer space.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…CoF2-MXene has a distinct shoulder to the (002) peak between 2θ = 0.5 -1.0°, reflecting the presence of a pillared structure. 27 Using this shoulder at 0.77° to calculate a c lattice parameter of 36 Å reveals layering with ultra-large interlayer spacing for CoF2-MXene. Smaller cations with lower charges, such as Na + or K + , lead to larger interlayer spaces than multivalent cations like Al 3+ due to their smaller hydration shell, allowing two layers of cations and associated water within an interlayer space.…”
Section: Resultsmentioning
confidence: 97%
“…15,18,25,26 We recently reported the unexpected structural heterogeneity of Ti3C2Tx MXene etched with CoF2/HCl, which has low AlF3•3H2O impurity. 27 We found that CoF2/HCl etching leads to Ti3C2Tx MXene with pillared layers. Removal of interlayer confined molecular water revealed two distinctive layering systems, specifically, (i) typical Ti3C2Tx MXene layers reduced the interlayer spacing upon water removal, and (ii) pillared Ti3C2Tx MXene layers that retained their open and large interlayer spacing even after deintercalation of water.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations